The Social Impact of Violent Theft on the Community's Sense of Security - Hamid, Abdul; Imraan , Mohd (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
Violent theft is a crime that has a serious impact on social life. It not only causes material loss and physical suffering for victims, but also has a broad impact on the community's sense of security and social order. The increase in violent theft cases tends to trigger fear, anxiety, and distrust in the community. These conditions can disrupt social activities, reduce the quality of interactions between residents, and weaken social cohesion within the community. This article aims to analyze the social impact of violent theft on the community's sense of security using a juridical-sociological approach. The discussion focuses on community perceptions of environmental security, changes in social behavior patterns, and the role of law enforcement in restoring public trust. The study's findings indicate that violent theft is not merely a criminal law issue, but also a social problem that requires comprehensive intervention through preventive, repressive, and participatory efforts to foster a sense of security and order in society.